2002
DOI: 10.1182/blood.v99.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytically inactive terminal complement complex causes transendothelial migration of polymorphonuclear leukocytes in vitro and in vivo

Abstract: Intravital microscopy was used to monitor leukocyte traffic across rat mesenteric postcapillary venules induced by the inactive terminal complement (C) complex (iTCC) topically applied to ileal mesentery. Leukocytes started rolling within 15 minutes from the administration of iTCC, and by 1 hour they adhered almost completely to the endothelium emigrating from the vessels in the next 3 hours. C5a caused a similar, though less marked, effect, whereas boiled iTCC was inactive, excluding the contribution of conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 47 publications
3
74
0
1
Order By: Relevance
“…First, MAC has been shown to cause proliferation of glomerular mesangial, endothelial, and epithelial cells in vitro and therefore may be directly involved in inducing a increase in intrinsic cell number (17,21,44,45). Additionally, there are data indicating that MAC can induce the synthesis and/or secretion of a number of proinflammatory cytokines such as TNF-␣ and IL-1 (22,44), adhesion molecules such as ICAM-1 and E selectin (23), and chemokines such as IL-8 (46) and that these effects may play a role in the infiltration of cells to the glomerulus. We have also demonstrated that later in the progression of ANTN, mCd59a deficiency, by allowing unregulated MAC deposition, exacerbates glomerular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, MAC has been shown to cause proliferation of glomerular mesangial, endothelial, and epithelial cells in vitro and therefore may be directly involved in inducing a increase in intrinsic cell number (17,21,44,45). Additionally, there are data indicating that MAC can induce the synthesis and/or secretion of a number of proinflammatory cytokines such as TNF-␣ and IL-1 (22,44), adhesion molecules such as ICAM-1 and E selectin (23), and chemokines such as IL-8 (46) and that these effects may play a role in the infiltration of cells to the glomerulus. We have also demonstrated that later in the progression of ANTN, mCd59a deficiency, by allowing unregulated MAC deposition, exacerbates glomerular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…mAb M89D3 to CD31 was kindly provided by M.R. Zocchi (San Raffaele Hospital, Milan, Italy) (Dobrina et al, 2002). Mouse IgG1 isotype control was from Sigma-Aldrich (Milano, Italy) and mAb MEM-G9 anti-human leukocyte antigen G (HLA-G) was a kind gift of P. Le Bouteiller (Toulouse, France).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Expression of adhesion molecules and tissue factor, release of chemokines, increased permeability are some of the responses of ECs to these factors (Bossi et al, 2004;Dobrina et al, 2002;Kilgore et al, 1996;Selvan et al, 1998) and both C5a and SC5b-9 have been shown to promote transendothelial migration of PMN (Dobrina et al, 2002). However, under normal conditions the endothelium is protected from the stimulating effect of C activation products that induce a pro-inflammatory and pro-coagulant state by the regulatory proteins CD46, CD55 and CD59 expressed on their surface and the fluid phase regulator Factor H that binds to ECs (Asch et al, 1986;Hamilton et al, 1990;Jokiranta et al, 2005;McNearney et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…HP-NAP (1 M) was added to the lower chamber, and after 45 min of incubation at 37°C, the PMNs were added to the endothelial layer and left for 30 min at 37°C. The adherent PMNs were fixed and processed for scanning microscopy, as described previously (28).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%